The effect of preconception housing and living conditions on primary infertility among couples in Gaza Strip, Palestine: A case-control study - Amal DHAIR; Yehia ABED (Journal of Health and Social Sciences)
Introduction: The aim of this study was to address the relationship between housing and living conditions that couples might experience before and after marriage and primary infertility in Gaza Strip, Palestine. Methods: A case-control study of 160 infertile couples matched residentially with 160 fertile ones was per- formed in Gaza Strip, Palestine. Infertile couples were chosen from list of patients registered in five fertility centers from 2016 to 2018. Data was collected through a self-administered questionnaire and analyzed through SPSS program version 22 by using descriptive analysis, cross-tabulation, and binary logistic regres- sion. Results: A positive association between using private vendors as a source of drinking water before marriage and primary infertility (P < 0.001) was demonstrated in females and males. Being a refugee (P = 0.036), living near borders (P = 0.011), living in extended families (P = 0.021), paying for rents (P = 0.029), and using septic porous sewer tanks (P = 0.020) provided a positive significant relationship after marriage. Odds of drinking water from rooming tanks before marriage was seven times risk in females (95% Confidential Interval [CI] 1.44 to 32.52, P = 0.020) mostly ovulatory and idiopathic causes, using septic sewer porous tanks held three times risk (95% CI 1.33 to 6.92, P = 0.008) mostly obstructive and ovulatory causes in ma- les and females, respectively and living in extended families held twice risk (95% CI, 1.20-3.56, P = 0.009) mostly nonobstructive causes in males and ovulatory and endometrial causes in females. Conclusion: Our findings provided evidence for the effect of inadequate living conditions on the fertility status of both women and men which opens the gate for further in-depth randomized trials.